Green synthesis of inorganic nanoparticles as therapeutic proposals for cancer: a review - Nunes de Godoi, Samantha; Binotto Fagan, Solange; Gomes, Patrícia; Ferreira Ourique, Aline (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Currently, the deliberate use of medications is discussed due to the resistance that patients have shown in relation to conventional treatments, addiction processes and often intoxication due to self-dosing. Seeking to minimize this tendency, many compounds of natural origin have been studied in an attempt to less toxic and less costly therapies, due to the fact that they are compounds present in nature in abundance. Obtained from natural compounds, extracts from plants have gained space in studies that seek new potential pharmacological applications. Nanosystems are known for their ability to add different potentials to compounds, such as increasing stability, protecting from degradation and minimizing possible adverse effects. Inorganic nanoparticles have gained space in the focus of cancer treatment, however, toxicological and biopersistent factors have caused discussions and led to the search for alternatives. Thus, the “green synthesis” arises, where natural products and other compounds, added to the production of this type of nanostructured systems would have the potential to add biocompatibility to nanoparticles, thus making possible therapeutics. In this context, a review study was carried out, using the Scopus database, which mentioned the application of extracts linked to the production of inorganic nanoparticles, in order to propose new treatments for cancer. As a result, we can observe that the use of inorganic nanoparticles production methods involving natural compounds is growing. This study aimed to encourage research that emphasizes the use of compounds of natural origin linked with nanotechnology, envisioning innovative and effective treatments against cancer.